Potenciais auditivos de longa latência para avaliação do tratamento medicamentoso do zumbido - Azevedo, Andreia Aparecida de [UNIFESP] (2018)
Objective: To verify if the Event related Potentials (ERP´s)) present changes in their latency and or amplitude that may help to measure, with the THI (Tinnitus Handicap Inventory) and the VAS (VisualAnalogue Scale) questionnaire, any characteristics objectives of a drug treatment for tinnitus. Method: Eightyeight patients complaining of tinnitus were randomized into two groups of drugs: Central drugs with different mechanisms of action in the neurotransmitters involved in the auditory pathways and a drug with Peripheric. Its effects on the negative reaction of the tinnitus symptom were evaluated by the eventrelated auditory potentials at three moments: premedication (T1), at the end of the drug treatment (T2) and after a washout period (T3) and compared with the results of the EVA and the THI questionnaire Results: Measurement of ERP´s waves in central and peripheral drugs did not show significant differences during the 03 evaluated moments (p = 0.53), despite the significant improvement in the evaluation of the THI questionnaire and in the EVA for tinnitus volume and annoyance (p< 0.0001). Conclusion: The use of ERP´s in patients with chronic tinnitus subjected to drug treatment of both central and peripheral action did not present changes in latency and amplitude of waves N1, P2, N2 and P3 throughout the treatment drugs when compared to Tinnitus handicap Inventory and the analog visual scale. The amplitude and latency parameters of Event Related Potentials can´t be considered as a criterion for evaluate the evolution of drug treatment in tinnitus complaint.